Book Reviews / Рецензии книг / Buchbesprechungen - Duc, Nguyen Tien; Jobst, Solvejg (International Dialogues on Education Journal, 2014)
Olaf Beuchling & Tuan Van Cong (2013): Vom Mekong an die Elbe. Buddhistisches Klosterleben in der vietnamesischen Diaspora / Xuôi dòng Cửu Long đậu bến Elbe. Nếp Chùa Việt trên đất khách. Charl Wolhuter, Nikolay Popov, Bruno Leutwyler & Klara Skubic Ermenc (Eds.) (2013): Comparative Education at Universities World Wide.